A concentrating photovoltaic/Kalina cycle coupled with absorption chiller. (15th August 2018) - Qu, Wanjun; Hong, Hui; Su, Bosheng; Tang, Sanli; Jin, Hongguang
Highlights: A concentrating photovoltaic/Kalina cycle with absorption chiller is described. Waste heat of PV produces cooling energy and then reduces turbine-outlet temperature. Increase in work is expected as result of the expansion ratio enhancement of turbine. Solar efficiency is increased by 10–60% compared to stand-alone concentrating PV. High-performance and high-reliability of PV in our hybrid system have been confirmed. Abstract: In this paper, we propose a concentrating photovoltaic/Kalina cycle having an absorption chiller. Here, the waste heat from photovoltaic cells can be recovered by an absorption chiller, and the produced cold energy is used to cool the turbine-outlet working fluid of the Kalina cycle. Compared with Kalina cycle without absorption chiller, output mechanical power from cycle can be increased due to the enhancement of turbine expansion ratio. A typical monocrystalline photovoltaic/Kalina cycle having absorption chiller is described. The influence of key parameters on the thermal performance is examined, such as photovoltaic temperature and direct normal irradiation. The results show that the waste heat with a temperature between 60 °C and 70 °C can be used for producing mechanical power by an efficiency among 4–5%. In comparison with the referenced Kalina cycle without further cooling the working fluid, the Kalina cycle having absorption chiller has a potential increase in the efficiency among 2–3%. As for the concentrating photovoltaics, the solar-to-electricity efficiency reaches about 24% while photovoltaic efficiency is about 4.2% without cooling. This work provides a new way to efficiently use the solar energy by combining photovoltaics and thermal cycles.